Coping with crises - "Parry, Glenys" (Hyderabad, 2000)
Intended for those involved in dealing with other people's crises, and their clients, this volume aims to provide a basic understanding of what a crisis is and how individuals respond to them. It also offers suggestions on how to help.
Keywords: Psychology